On the Possibility of Indirect Determination of the Glass Transition Temperature of Proteins from Viscosity Measurements and Avramov’s Model - Monkos, Karol (Current Topics in Biophysics, 2015)
The paper presents the results of viscosity determinations on aqueous solutions of hen egg-white lysozyme, bovine ß-lactoglobulin, human and porcine immunoglobulin IgG at a wide range of concentrations and at temperatures ranging from 5oC to 55oC. Viscosity-temperature dependence of the proteins solutions is analyzed based on a formula resulting from the Avramov's model. One of the parameters in the Avramov's equation is the glass transition temperature Tg. It turns out that for all studied proteins, the Tg of the solution increases with increasing concentration. To determine the glass transition temperature of the dry protein Tg,p, a modified form of the Gordon-Taylor equation is used. This equation gives the relationship between Tg and the concentration of the solution, and Tg,p and a parameter dependent on the strength of protein-solvent interaction are fitting parameters. Thus determined the glass transition temperature for the studied dry proteins is in the range from 227.3 K (for bovine ß-lactoglobulin) to 260.6 K (for hen egg-white lysozyme).